Immunogenicity and safety of a RBD vaccine against SARS-CoV-2 in a murine model. Issue 49 (September 2022) - Díaz, Andrés; Serrano-Coll, Héctor; Botero, Yesica; Calderón, Alfonso; Arteta-Cueto, Ariel; Gastelbondo, Bertha; Guzmán, Camilo; Rivero, Ricardo; Martínez, Caty; Marquez, Tania; Arrieta, Germán; Mattar, Salim
Abstract: Introduction: Although more than half of the world's population is already vaccinated, the appearance of new variants of concern puts public health at risk due to the generation of new immunogens against the virus as a crucial and relevant strategy in the control of these new variants. Methods: A preclinical study used a potential vaccine candidate (RBD, SARS-CoV-2). Four groups of BALB/c mice were used, a control group, an adjuvant group, a group inoculated with one dose of RBD subunit protein, and the fourth group inoculated with two doses of RBD subunit protein. Results: No inflammatory or cellular changes were shown in the mice's anatomopathological evaluation. Higher kinetics and 75% seroconversion were obtained in the mice inoculated with two doses of RBD (P < 0.0001). Conclusions: The application of two doses of the RBD vaccine candidate in BALB/c mice proved safe and immunogenic against SARS-CoV-2.